Envisager une ethnographie énactive ? Réflexions illustrées - Guillaume Azéma; Mélanie Secheppet; Anne-Marie Mottaz (Activités, 2020)
As a contribution to reflections on the elaboration of an enactive ethnography, this article questions the place and role of standard ethnographic methods in the Course-of-Action Research Programme (CARP). It points out both the compatibilities and the theoretical differences between the ontology which presides over field surveys and that which underpins the research carried out within the CARP framework. Using illustrations drawn from empirical research, it attempts to specify the ways in which it appears possible to work on the basis of the construction and analysis of psycho-phenomenological and/or ethnographic data. Overall, this text aims at proposing means that have been developed, or are being developed, by researchers interested in ensuring the primacy of the activity. It argues that ideally these means consist of a dialectic between intrinsic and extrinsic data that are concerned with the intrinsic.